Production of thermoplastic towpregs - Velosa, J. C. (2010)
This work establishes process windows for efficient towpreg production on a developed powder coating equipment. Three different thermoplastic towpregs were studied: one for highly demanding markets (carbon fibre/PrimospireTMPR-120) and other two for commercial applications (glass/polypropylene and glass/polyvinyl chloride). Mechanical properties of compression moulded composites obtained from the produced towpregs were also obtained and discussed.